Multilayer coating film forming method and multilayer coating film

By using a combination of aqueous resin and titanium oxide coated alumina sheet pigment in automotive coating, combined with standstill and low-temperature heating processes, the difficulty in maintaining coating performance and design improvement in the prior art is solved, and high brightness is achieved And the white multi-layer coating effect with different colors.

CN119255873APending Publication Date: 2025-01-03KANSAI PAINT CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380042737.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-07
Filing Date
2023-06-06
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The prior art is difficult to maintain coating performance at low temperatures in automotive coatings, and there is still room for improvement in high brightness and angular heterochromatic design, especially in integrated coatings of plastic and metal components.

Method used

The multi-layer coating method is used to form a multi-layer coating using a water-based two-liquid first coloring coating, a water-based single-liquid white coating, an aqueous single-liquid interference color coating and a solvent-based two-component transparent coating. It is cured by standing and low-temperature heating and using Titanium oxide coats alumina sheet pigment and a hydroxyl-containing resin to form an excellent white multi-layer coating film.

Benefits of technology

It has achieved the formation of a white multi-layer coating film with low-temperature curability, excellent appearance and design of the finished product on the metal and plastic components of the automotive exterior panel, improving the brightness, brightness and granularity of the coating film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005151498400000181
    Figure BDA0005151498400000181
  • Figure BDA0005151498400000191
    Figure BDA0005151498400000191
  • Figure BDA0005151498400000231
    Figure BDA0005151498400000231
Patent Text Reader

Abstract

The present invention is a method for forming a multilayer coating film, the method comprising: a step (1) for forming an uncured first colored coating film by applying an aqueous two-pack type first colored coating material (X) on an automobile outer panel; a step (2) for forming an uncured white coating film by applying an aqueous one-pack white coating material (Y-1) on the uncured first colored coating film; a step (3) in which the uncured white coating film is left to stand for 4 minutes or more and the solid content of the coated coating film is 50 mass% or more; a step (4) for forming an uncured interference color coating film by applying an aqueous one-pack interference color coating material (Y-2) on the uncured white coating film having a solid content of 50 mass% or more; a step (5) for forming an uncured clear coating film by applying a solvent-based two-component clear coating material (Z) on the uncured interference color coating film; and a step (6) in which the coating film formed in steps (1) to (5) is heated at 75-100 DEG C and cured at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for forming a multilayer coating film and a multilayer coating film. Background Art

[0002] In automobile painting, a method of forming a multilayer coating film by a 3-coat 2-bake (3C2B) method is widely used, which includes the following steps in order: application of a midcoat, baking and curing, application of a water-based base coating, preheating (preheating), application of a clear coating, and baking and curing after applying an electrodeposition coating to the object. However, in recent years, from the viewpoint of energy saving, the baking and curing step after the midcoat is applied has been omitted, and the 3-coat 1-bake (3C1B) method has been tried, which includes the following steps in order: application of a water-based midcoat, preheating (preheating), application of a water-based base coating, preheating (preheating), application of a clear coating, and baking and curing after applying an electrodeposition coating to the object.

[0003] In recent years, in order to reduce the equipment cost in the manufacturing process of automobile outer panels and to make the color tones of metal components and plastic components consistent, a method of integrally painting a plastic component while it is attached to a metal component has been required.

[0004] For example, Patent Document 1 discloses a method for painting an automobile body, which is characterized in that, in a method for continuously painting an automobile body, after the body is primed, a resin component is installed, a conductive primer is mainly applied to the resin component, then a mid-coat is applied, and further a top-coat is applied to paint the resin component and the body as a whole.

[0005] In addition, Patent Document 2 discloses a method for forming a multilayer coating film, characterized in that a water-based mid-coat coating is applied to a substrate having both a steel plate and a plastic substrate to form a mid-coat coating film, a water-based base coating is applied to the formed mid-coat coating film to form a base coating film, and then an organic solvent-based clear coating is applied to form a clear coating film, and the three layers of the mid-coat coating film, the base coating film and the clear coating film are heated and cured, wherein the water-based base coating contains (a) 10 to 60% by mass of an acrylic resin emulsion obtained by emulsion polymerization of a monomer mixture containing 0.2 to 20% by mass of a cross-linking monomer, (b) 5 to 40% by mass of a water-soluble acrylic resin in terms of solid content, (c) 20 to 40% by mass of a melamine resin in terms of solid content, and (d) 10 to 40 parts by mass of propylene glycol monoalkyl ether relative to 100 parts by mass of the coating resin solid content.

[0006] On the other hand, in the exterior colors of industrial products such as automobiles, the color appearance of the coating that changes according to the viewing angle, that is, the color that is high brightness (when the coating is observed near the regular reflected light) and changes greatly when the angle changes from high brightness to dimness (when the coating is observed from an oblique direction) is called a coating with high angular color variation, which has the effect of making the shape of industrial products stand out and is in high demand. In addition, white pearl color is a popular color because it produces a sense of luxury, but in recent years, the above-mentioned white pearl color with high angular color variation has been required. For example, Patent Documents 3 and 4 disclose a method for forming a white pearl coating film, which can obtain a pearlescent coating film with high angular color variation and excellent white pearl feeling.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent document 1: Japanese Patent Application Publication No. 61-74682;

[0010] Patent Document 2: Japanese Patent Application Publication No. 2011-131135;

[0011] Patent Document 3: Japanese Patent Application Publication No. 2006-326538;

[0012] Patent document 4: International Publication No. 2021 / 014859. Summary of the invention

[0013] Problems to be solved by the invention

[0014] If the baking temperature is lowered by the methods described in Patent Documents 1 and 2, it is difficult to ensure coating film properties such as finished product appearance and water resistance. In addition, from the viewpoint of further reducing energy consumption, an integrated coating system that maintains coating film properties and cures at a lower temperature is required.

[0015] In addition, although the inventions described in Patent Documents 3 and 4 have high design properties such as high brightness and angle-dependent color flop, there is still room for further improvement.

[0016] The present invention has been completed in view of the above situation, and an object of the present invention is to provide a multi-layer coating film forming method and a multi-layer coating film formed by the forming method, wherein the multi-layer coating film forming method forms a white multi-layer coating film with excellent low-temperature curing properties, finished product appearance, and design properties on both metal components and plastic components of automobile outer panels.

[0017] Means for solving problems

[0018] The present invention is a method for forming a multilayer coating film, characterized in that it comprises: a step (1) of coating a first water-based two-component coloring paint (X) on two members of a metal member and a plastic member of an automobile outer panel to form an uncured first coloring paint film; a step (2) of coating a water-based one-component white coating (Y-1) on the uncured first coloring paint film obtained in the step (1) to form an uncured white coating film; a step (3) of setting the uncured white coating film obtained in the step (2) so that the solid content of the applied coating film is 50% by mass or more; a step (4) of drying the solid content obtained in the step (4) to form an uncured white coating film; The invention further comprises a step (4) of coating an uncured white coating film containing 50% by mass or more of a water-based one-component interference color coating material (Y-2) to form an uncured interference color coating film; a step (5) of coating the uncured interference color coating film obtained in the step (4) with a solvent-based two-component clear coating material (Z) to form an uncured clear coating film; and a step (6) of simultaneously curing the uncured first colored coating film, the uncured white coating film, the uncured interference color coating film and the uncured clear coating film formed in the steps (1) to (5) by heating at a temperature of 75° C. to 100° C., wherein the water-based one-component interference color coating material (Y-2) contains 50% by mass or more of a water-based one-component interference color coating material (Y-2) to form an uncured interference color coating film. The invention relates to a solvent-based two-component clear coating material (Z) comprising a hydroxyl-containing acrylic resin (Z1) and a polyisocyanate compound (Z2), wherein the amount of the hydroxyl-containing acrylic resin (Z1) is 15 parts by mass or more and 21 parts by mass or less based on 100 parts by mass of the carrier-forming resin (A), the amount of the hydroxyl-containing aluminum oxide flake pigment (B) is 18 parts by mass or more and 22 parts by mass or less, the cured film thickness of the interference color coating film is 4 parts by mass or more and 7 parts by mass or less, and the solvent-based two-component clear coating material (Z) comprises a hydroxyl-containing acrylic resin (Z1) and a polyisocyanate compound (Z2), wherein the amount of the hydroxyl-containing acrylic resin (Z1) is 10 parts by mass or more and the amount of the polyisocyanate compound (Z2 ... The present invention relates to a multi-layer coating film comprising a polyisocyanate compound (Z2) having a uretdione structure and a trimer or higher compound of a diisocyanate in a ratio of 10 / 90 to 50 / 50 in terms of solid content mass ratio, and the formed multi-layer coating film has a brightness L* (15°) of 113 to 120, a luminous intensity Si (45°) of 3 to 5, and a reciprocal of a graininess 1 / G of 0.4 to 0.5 when measured using a multi-angle colorimeter.

[0019] The aqueous one-component white paint (Y-1) contains a hydroxyl-containing polyester resin (Y1), a hydroxyl-containing acrylic resin (Y2), a hydroxyl-containing polyurethane resin (Y3) and a melamine resin (Y4), and the water absorption of the uncured white coating film at 20° C. is preferably 6.5% or less.

[0020] The plastic component is preferably pre-coated with a primer.

[0021] The plastic member is preferably composed of a composite material of a polyamide resin and a modified polyphenylene ether resin.

[0022] The solvent-based two-pack clear coating material (Z) preferably further contains polysiloxane-modified silica particles (Z3) having an average primary particle size of 1 nm or more and 40 nm or less.

[0023] The multilayer coating film of the present invention is obtained by the multilayer coating film forming method of the present invention.

[0024] In addition, the multilayer coating of the present invention is formed by sequentially arranging an uncured white coating, an uncured interference color coating, and an uncured transparent coating, and then curing these coatings simultaneously, so it is presumed that a region formed by mixing a portion of the composition of each coating is formed at the interface of the coating. In addition, the cured product contains a polymer, so it is difficult to determine the structure of the multilayer coating by a general formula, etc., and it is also difficult to determine it based on the characteristics of the multilayer coating. That is, the multilayer coating of the present invention can be determined for the first time by the multilayer coating formation method in the present invention.

[0025] Therefore, for the multilayer coating film of the present invention, there are cases where it cannot be directly determined from its structure or characteristics or it is almost impractical.

[0026] Effects of the Invention

[0027] According to the method of the present invention, a white multilayer coating film having low-temperature curability and excellent finished appearance and design properties can be formed on both metal parts and plastic parts of automobile outer panels. DETAILED DESCRIPTION

[0028] Hereinafter, the multilayer coating film forming method of the present invention will be described in order for each step.

[0029] [Process (1)]

[0030] In step (1) of the present invention, the aqueous two-component first colored paint (X) is applied to both the metal member and the plastic member of the automobile outer panel to form an uncured first colored coating film.

[0031] Examples of the material of the metal parts include iron, aluminum, brass, copper, tin plating, stainless steel, galvanized steel, and zinc alloy (e.g., Zn-Al, Zn-Ni, and Zn-Fe, etc.) plated steel, etc. The metal parts are preferably subjected to surface treatment such as phosphate treatment, chromate treatment, and composite oxide treatment, and are more preferably subjected to cationic electrodeposition coating.

[0032] As materials for plastic components, for example: polyolefins (co)polymerized from one or more olefins having 2 to 10 carbon atoms such as ethylene, propylene, butene, hexene, etc.; polycarbonate, ABS resin, polyurethane resin, polyamide resin, composite materials of polyamide resin and modified polyphenylene ether resin, etc. As plastic parts, for example, bumpers, spoilers, grilles, fenders, etc. can be cited. These plastic components can be primed as needed. As primers, primers known in the past, such as chlorinated polyolefins, blocked isocyanate resins, epoxy resins, etc., can be used.

[0033] The above-mentioned metal components and plastic components can be assembled by known methods.

[0034] The aqueous two-component first colored paint (X) preferably contains a hydroxyl-containing polyester resin (X1), a hydroxyl-containing acrylic resin (X2), a hydroxyl-containing polyurethane resin (X3) and a polyisocyanate compound (X4) as film-forming components. From the viewpoint of low-temperature curability, the isocyanate group in the polyisocyanate compound (X4) is preferably contained in a ratio of 1.5 equivalents or more and 2.0 equivalents or less, and more preferably in a ratio of 1.5 equivalents or more and 1.9 equivalents or less, relative to 1 equivalent of hydroxyl groups in the hydroxyl-containing polyester resin (X1), the hydroxyl-containing acrylic resin (X2) and the hydroxyl-containing polyurethane resin (X3).

[0035] The hydroxyl-containing polyester resin (X1) generally includes a product obtained by neutralizing a polyester resin prepared by an esterification reaction using a polyol and a polyacid, and if necessary, a monoacid, an oil component (including the fatty acid), etc. The weight average molecular weight of the polyester resin is generally in the range of about 3,000 to 100,000, preferably 4,000 to 70,000, and more preferably 5,000 to 30,000.

[0036] Examples of the polyol include ethylene glycol, diethylene glycol, propylene glycol, butanediol, pentanediol, hexanediol, 2,2-dimethylpropanediol, glycerol, trimethylolpropane, pentaerythritol, and ethylene oxide adducts or propylene oxide adducts of bisphenol compounds. These may be used alone or in combination of two or more.

[0037] Examples of the polyacid include phthalic acid, isophthalic acid, tetrahydrophthalic acid, hexahydrophthalic acid, maleic acid, succinic acid, adipic acid, sebacic acid, trimellitic acid, pyromellitic acid, and anhydrides thereof. Examples of the monoacid include benzoic acid and tert-butylbenzoic acid, and examples of the oil component include castor oil, dehydrated castor oil, safflower oil, soybean oil, linseed oil, tall oil, coconut oil, and fatty acids thereof, and these may be used alone or in combination of two or more.

[0038] In the above polyester resin, the introduction of carboxyl groups can be carried out by, for example, using a polyacid such as trimellitic acid or pyromellitic acid having three or more carboxyl groups in one molecule as part of the polyacid component, or performing half-ester addition of a dicarboxylic acid. In addition, the introduction of hydroxyl groups can be easily carried out by, for example, using a polyol such as glycerol or trimethylolpropane having three or more hydroxyl groups in one molecule as part of the polyol component.

[0039] The carboxyl groups of the hydroxyl-containing polyester resin (X1) can be neutralized with an alkaline substance. As the alkaline substance, a water-soluble substance is preferred, for example, ammonia, methylamine, ethylamine, propylamine, butylamine, dimethylamine, trimethylamine, triethylamine, ethylenediamine, morpholine, methylethanolamine, dimethylethanolamine, diethanolamine, triethanolamine, diisopropanolamine, 2-amino-2-methylpropanol, etc., and these can be used alone or in combination of two or more.

[0040] The hydroxyl-containing polyester resin (X1) preferably has an acid value in the range of usually 10 mgKOH / g to 100 mgKOH / g, further in the range of 20 mgKOH / g to 80 mgKOH / g, particularly in the range of 20 mgKOH / g to 50 mgKOH / g, and a hydroxyl value in the range of usually 10 mgKOH / g to 300 mgKOH / g, further in the range of 30 mgKOH / g to 200 mgKOH / g, particularly in the range of 50 mgKOH / g to 200 mgKOH / g.

[0041] The hydroxyl-containing acrylic resin (X2) is obtained by copolymerizing a monomer mixture consisting of a hydroxyl-containing polymerizable unsaturated monomer, a hydrophilic group-containing polymerizable unsaturated monomer such as a carboxyl-containing polymerizable unsaturated monomer, and other polymerizable unsaturated monomers, and examples thereof include a water-soluble acrylic resin having a weight average molecular weight of 5,000 to 100,000, preferably 10,000 to 90,000, and more preferably 20,000 to 80,000, and an acrylic resin emulsion having a weight average molecular weight of 50,000 to 50,000, preferably 75,000 to 50,000, and more preferably 100,000 to 100,000.

[0042] Examples of the hydroxyl-containing polymerizable unsaturated monomer include hydroxyalkyl esters of acrylic acid or methacrylic acid such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; polyethylene glycol (meth)acrylate, polypropylene glycol (meth)acrylate, and the like, and these may be used alone or in combination of two or more.

[0043] Examples of the carboxyl group-containing polymerizable unsaturated monomer include (meth)acrylic acid, crotonic acid, maleic acid, fumaric acid, itaconic acid, and semi-alkyl esters of dicarboxylic acids thereof. Examples of the hydrophilic group-containing polymerizable unsaturated monomer other than those mentioned above include polyalkylene chain-containing polymerizable unsaturated monomers such as polyethylene glycol (meth)acrylate and polypropylene glycol (meth)acrylate.

[0044] Examples of the other polymerizable unsaturated monomers include alkyl or cycloalkyl (meth)acrylates having 1 to 24 carbon atoms such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, cyclohexyl (meth)acrylate, lauryl (meth)acrylate, and isobornyl (meth)acrylate; hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; glycidyl (meth)acrylate, acrylonitrile, acrylamide, styrene, vinyltoluene, vinyl acetate, vinyl chloride, and 1,6-hexanediol diacrylate, and these may be used alone or in combination of two or more.

[0045] The copolymerization of the monomer mixture can be carried out by a known method per se, for example, by solution polymerization when a water-soluble acrylic resin is desired, or by emulsion polymerization when an acrylic resin emulsion is desired.

[0046] When the hydroxy-containing acrylic resin (X2) is an acrylic resin emulsion obtained by emulsion polymerization, it may be an emulsion in the form of multilayered particles obtained by emulsion polymerization of a monomer mixture in the presence of water and an emulsifier in multiple stages.

[0047] The carboxyl group of the hydroxyl-containing acrylic resin (X2) may be neutralized using the above-mentioned basic substance as required.

[0048] The hydroxyl-containing acrylic resin (X2) preferably has an acid value in the range of usually 10 mgKOH / g to 100 mgKOH / g, further in the range of 15 mgKOH / g to 80 mgKOH / g, particularly in the range of 20 mgKOH / g to 60 mgKOH / g, and a hydroxyl value in the range of usually 10 mgKOH / g to 250 mgKOH / g, further in the range of 20 mgKOH / g to 200 mgKOH / g, particularly in the range of 30 mgKOH / g to 150 mgKOH / g.

[0049] The hydroxyl-containing polyurethane resin (X3) can preferably be a hydrophilic polyurethane resin that can be dissolved or dispersed in water. For example, it is preferably an aqueous dispersion of a self-emulsifying polyurethane resin having an average particle size of about 0.001 μm to about 1.0 μm, especially 0.02 μm to about 0.3 μm, obtained by reacting dimethylolalkanoic acid usually at an NCO / OH equivalent ratio of 1 / 0.5 to 1 / 0.95, especially 1 / 0.6 to 1 / 0.9 by a one-step method or a multi-stage method to obtain a urethane prepolymer, which is obtained by chain extension and emulsification after or during neutralization, especially by distilling off a part or all of the organic solvent used in the production process.

[0050] The hydroxyl-containing polyurethane resin (X3) preferably has an acid value in the range of usually 10 mgKOH / g to 60 mgKOH / g, further in the range of 20 mgKOH / g to 50 mgKOH / g, particularly in the range of 20 mgKOH / g to 40 mgKOH / g, and a hydroxyl value in the range of usually 10 mgKOH / g to 60 mgKOH / g, further in the range of 20 mgKOH / g to 50 mgKOH / g, particularly in the range of 20 mgKOH / g to 40 mgKOH / g.

[0051] The polyisocyanate compound (X4) is a compound having at least two unblocked isocyanate groups in one molecule, and examples thereof include aliphatic polyisocyanates, alicyclic polyisocyanates, aromatic aliphatic polyisocyanates, aromatic polyisocyanates, derivatives of the polyisocyanates, etc. Examples of the derivatives of the polyisocyanates include dimers, trimers, biuret, allophanate, uretdione, isocyanurate, etc. of the above-mentioned polyisocyanates.

[0052] The above-mentioned polyisocyanates and their derivatives may be used alone or in combination of two or more thereof. In addition, among these polyisocyanates, it is preferred to use aliphatic diisocyanates, alicyclic diisocyanates and their derivatives alone or in combination of two or more thereof.

[0053] In addition, as the polyisocyanate compound (X4), from the viewpoint of the smoothness of the obtained coating film, a water-dispersible polyisocyanate compound is preferably used. As the water-dispersible polyisocyanate compound, any polyisocyanate compound that can be stably dispersed in an aqueous medium can be used without restriction, among which, a hydrophilic polyisocyanate compound (X4-1) modified to be hydrophilic, a polyisocyanate compound (X4) and a surfactant premixed to impart water dispersibility, etc. can be suitably used.

[0054] Examples of the hydrophilized polyisocyanate compound (X4-1) include an anionic hydrophilized polyisocyanate compound (X4-1-1) obtained by reacting an active hydrogen group of an active hydrogen group-containing compound having an anionic group with an isocyanate group of a polyisocyanate compound, and a nonionic hydrophilized polyisocyanate compound (X4-1-2) obtained by reacting a hydrophilic polyether alcohol such as a polyoxyethylene monool with a polyisocyanate compound. These compounds may be used alone or in combination of two or more.

[0055] The above-mentioned active hydrogen group-containing compound having an anionic group includes a compound having an anionic group such as a carboxyl group, a sulfonic acid group, a phosphoric acid group, a group containing a betaine structure and having an active hydrogen group (such as a hydroxyl group, an amino group, etc.) that can react with an isocyanate group, and by reacting the compound with a polyisocyanate compound, hydrophilicity can be imparted to the polyisocyanate compound. As the anionic hydrophilized polyisocyanate compound (X4-1-1), a compound having a sulfonic acid group is particularly preferred.

[0056] The aqueous two-component first colored paint (X) may contain, as necessary, pigments such as coloring pigments and extender pigments, a curing agent other than the polyisocyanate compound (X4) such as a melamine resin, a curing catalyst, a thickener, an ultraviolet absorber, a light stabilizer, a defoaming agent, a plasticizer, an organic solvent, a surface conditioner, an anti-settling agent and other paint additives.

[0057] The aqueous two-component first coloring paint (X) can be applied to the object by a known method such as air spray coating, airless spray coating, rotary atomization coating, curtain coating, etc., and electrostatic application can be performed during coating. Among them, air spray coating, rotary atomization coating, etc. are preferred. The coating amount is usually 10 μm or more and 50 μm or less, preferably 10 μm or more and 40 μm or less in terms of cured film thickness.

[0058] [Step (2)]

[0059] In the step (2) of the present invention, the aqueous one-component white coating material (Y-1) is applied on the uncured first colored coating film obtained in the step (1) to form an uncured white coating film.

[0060] The aqueous one-component white paint (Y-1) used in the present invention preferably contains a hydroxyl-containing polyester resin (Y1), a hydroxyl-containing acrylic resin (Y2), a hydroxyl-containing polyurethane resin (Y3) and a melamine resin (Y4).

[0061] The aqueous one-pack type white paint (Y-1) can be prepared by dispersing a coloring component such as a coloring pigment and a bright pigment together with these resin components in an aqueous medium.

[0062] As the hydroxyl-containing polyester resin (Y1), the hydroxyl-containing acrylic resin (Y2) and the hydroxyl-containing polyurethane resin (Y3), the resins described above for the hydroxyl-containing polyester resin (X1), the hydroxyl-containing acrylic resin (X2) and the hydroxyl-containing polyurethane resin (X3) can be used as appropriate.

[0063] As the melamine resin (Y4), a butyl / methyl mixed etherified melamine resin having a weight average molecular weight in the range of 1500 to 3000, preferably 1500 to 2500, more preferably 1500 to 2000. In the mixed etherified melamine resin, the molar ratio of the butyl ether group to the methyl ether group is preferably usually in the range of 4 / 6 to 9 / 1, particularly in the range of 5 / 5 to 9 / 1.

[0064] Examples of the coloring pigment used in the aqueous one-component white paint (Y-1) include titanium oxide, zinc oxide, and carbon black.

[0065] The aqueous one-component white paint (Y-1) may contain appropriate paint additives such as an extender pigment, a curing agent other than the melamine resin (Y4), a curing catalyst, a thickener, an ultraviolet absorber, a light stabilizer, a defoaming agent, a plasticizer, an organic solvent, a surface conditioner, and an anti-settling agent, as required.

[0066] The water-based single-liquid white paint (Y-1) can be applied on the first coloring coating film by a method known per se, such as air spray coating, airless spray coating, rotary atomization coating, curtain coating, etc., and electrostatic application can be performed during coating. Among them, air spray coating, rotary atomization coating, etc. are preferred. The coating amount is usually preferably 5 μm or more and 30 μm or less, and more preferably 10 μm or more and 20 μm or less in terms of cured film thickness.

[0067] In the present invention, the water absorption of the uncured white coating film of the aqueous one-component white coating material (Y-1) at 20° C. is desirably 6.5% or less in view of the appearance of the finished product.

[0068] In addition, the water absorption of the uncured white coating film is measured as follows. The mass (W1) is measured in advance along with the regular coating plate coating, and the water-based single-component white coating (Y-1) is also coated on an OHP film (XEROX FILM No. V515, manufactured by Fuji XEROX Co., Ltd.) cut into a size of 10 cm × 15 cm. After preheating as needed, the mass (W2) of the OHP film coated with the water-based single-component white coating (Y-1) is measured in accordance with the time of coating the clear coating. Then, the OHP film coated with the water-based single-component white coating (Y-1) is immersed in deionized water at 20°C for 5 minutes and then taken out, and the mass (W3) of the film after the excess water attached to the film is gently wiped off with filter paper is measured. The water absorption is calculated by the following formula (1) based on the mass measurement results of W1 to W3.

[0069] Water absorption (%) = {(W3-W2) / (W2-W1)}×100(1)

[0070] [Step (3)]

[0071] In the step (3) of the present invention, the uncured white coating film obtained in the step (2) is allowed to stand until the solid content of the coating film becomes 50% by mass or more.

[0072] In addition, the "applied coating film" in the step (3) refers only to the uncured white coating film obtained after the uncured white coating film is left to stand.

[0073] The standing is generally performed at room temperature, for example, about 24° C. and about 70% humidity. The standing time is not particularly limited, but can be 4 minutes or more so that the solid content of the coating film is 50% by mass or more.

[0074] The solid content in the coating film is increased by leaving it to stand instead of preheating (preheating), so energy consumption is reduced.

[0075] Furthermore, by setting the solid content of the applied coating film to 50% by mass or more, intermixing of the white coating film and the interference color coating film described below can be suppressed, and a white multilayer coating film having excellent finished appearance and design properties can be formed.

[0076] [Step (4)]

[0077] In step (4) of the present invention, the aqueous one-component interference color coating material (Y-2) is applied onto the uncured white coating film having a solid content of 50% by mass or more obtained in step (3) to form an uncured interference color coating film.

[0078] The aqueous one-component interference color coating material (Y-2) contains a vehicle-forming resin (A) and a titanium oxide-coated aluminum oxide flake pigment (B) having an average particle diameter in the range of 10 μm or more and 14 μm or less.

[0079] As the carrier-forming resin (A), a base resin and a crosslinking agent are preferably used in combination. As the base resin, for example, acrylic resin, polyester resin, alkyd resin, polyurethane resin, etc. can be used, and they can be used alone or in combination of two or more. The base resin preferably has a crosslinking functional group such as a hydroxyl group.

[0080] As the crosslinking agent, for example, amino resins, polyisocyanate compounds, blocked polyisocyanate compounds, epoxy-containing compounds, carboxyl-containing compounds, carbodiimide-containing compounds, hydrazide-containing compounds, semicarbazide-containing compounds, etc. are cited. Among them, amino resins, polyisocyanate compounds and blocked polyisocyanate compounds that can react with hydroxyl groups, and carbodiimide-containing compounds that can react with carboxyl groups are preferred. The above crosslinking agents can be used alone or in combination of two or more.

[0081] The aqueous single-liquid interference color coating (Y-2) contains 15 parts by mass or more and 21 parts by mass or less of titanium oxide-coated aluminum oxide flake pigment (B) having an average particle size of 10 μm or more and 14 μm or less, based on 100 parts by mass of the carrier-forming resin (A), and the coating solid content is 18% by mass or more and 22% by mass or less.

[0082] The carrier-forming resin (A) can be used by being dissolved or dispersed in a solvent such as an organic solvent and / or water.

[0083] The titanium oxide-coated alumina flake pigment (B) is a pigment produced by uniformly coating natural or synthetic alumina flakes (alumina: Al 2 O 3 ) with a metal oxide having titanium oxide (TiO 2 ) as a main component, thereby expressing interference color.

[0084] From the viewpoint of forming a white multilayer coating film having excellent design properties, the cured film thickness of the interference color coating film is 4 μm or more and 7 μm or less.

[0085] [Step (5)]

[0086] In step (5) of the present invention, a solvent-based two-component clear coating material (Z) is applied onto the uncured interference color coating film obtained in step (4) to form an uncured clear coating film.

[0087] The solvent-based two-pack clear coating material (Z) contains isocyanate groups in the polyisocyanate compound (Z2) in a ratio of 1.5 equivalents to 2.0 equivalents per 1 equivalent of hydroxyl groups in the hydroxyl-containing acrylic resin (Z1).

[0088] The hydroxyl-containing acrylic resin (Z1) can be generally produced by copolymerizing a hydroxyl-containing unsaturated monomer and other unsaturated monomers copolymerizable with the monomer by conventional methods. The hydroxyl-containing unsaturated monomer is a compound having at least one hydroxyl group and a polymerizable unsaturated bond in one molecule, for example, monoesters of (meth)acrylic acid and a diol having 2 to 8 carbon atoms, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; ε-caprolactone-modified monoesters of (meth)acrylic acid and a diol having 2 to 8 carbon atoms; allyl alcohol; (meth)acrylates having a polyoxyethylene chain with a hydroxyl group at the molecular end; and the like.

[0089] Examples of other unsaturated monomers copolymerizable with the hydroxyl-containing unsaturated monomers include alkyl or cycloalkyl (meth)acrylates having 1 to 24 carbon atoms such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, cyclohexyl (meth)acrylate, lauryl (meth)acrylate, and isobornyl (meth)acrylate; (meth)acrylic acid, maleic acid, crotonic acid, β-carboxyethyl acrylate; glycidyl (meth)acrylate, acrylonitrile, acrylamide, styrene, vinyltoluene, and the like, and these may be used alone or in combination of two or more.

[0090] From the viewpoint of the finished product appearance such as smoothness and distinctness of image and the coating film performance such as weather resistance, the hydroxyl-containing acrylic resin (Z1) preferably has a hydroxyl value of 80 mgKOH / g or more and 200 mgKOH / g or less, further 90 mgKOH / g or more and 170 mgKOH / g or less, particularly 100 mgKOH / g or more and 140 mgKOH / g or less, and preferably has an acid value of 1 mgKOH / g or more and 40 mgKOH / g or less, further 3 mgKOH / g or more and 30 mgKOH / g or less, particularly 5 mgKOH / g or more and 20 mgKOH / g or less. In addition, from the viewpoint of the finished product appearance such as smoothness and distinctness of image and the coating film performance such as weather resistance, the hydroxyl-containing acrylic resin (Z1) preferably has a weight average molecular weight of 4000 or more and 20000 or less, further 6000 or more and 16000 or less, particularly 8000 or more and 12000 or less.

[0091] The polyisocyanate compound (Z2) contains a polyisocyanate compound having a uretdione structure and a compound that is a trimer or higher of a diisocyanate in a solid content mass ratio of 10 / 90 to 50 / 50, preferably 15 / 85 to 40 / 60, and more preferably 15 / 85 to 35 / 65. When the content ratio of the polyisocyanate compound having a uretdione structure to the compound that is a trimer or higher of a diisocyanate is outside the above range, the curability of the multilayer coating film finally formed becomes insufficient, and the coating film performance becomes insufficient, so it is not preferred.

[0092] As the polyisocyanate compound with uretdione structure, the uretdione body of hexamethylene diisocyanate manufactured by a method known per se is preferred. In addition, as the compound above the trimer of diisocyanate, for example, isocyanurate body, biuret body, allophanate body etc. of diisocyanates such as hexamethylene diisocyanate, isophorone diisocyanate can be used.

[0093] Regarding the usage ratio of the hydroxyl-containing acrylic resin (Z1) and the polyisocyanate compound (Z2), from the viewpoint of ensuring the curability of the multilayer coating film, it is preferred to select a ratio in which the isocyanate group in the polyisocyanate compound (Z2) is 1.5 equivalents or more and 1.9 equivalents or less relative to 1 equivalent of hydroxyl group in the hydroxyl-containing acrylic resin (Z1).

[0094] From the viewpoint of scratch resistance, the solvent-based two-pack type clear coating material (Z) may contain polysiloxane-modified silica particles (Z3) having an average primary particle size of 1 to 40 nm, as required.

[0095] The polysiloxane-modified silica particles (Z3) are silica particles having a structure in which the particle surface is modified with a polysiloxane chain. Conventionally known particles can be used, and commercially available products include "NANOBYK-3650", "NANOBYK-3651", and "NANOBYK-3652" (all trade names, manufactured by BYK).

[0096] The average primary particle size refers to a particle size (D50) at which the cumulative particle size distribution from the smaller particle size side in the volume-based particle size distribution is 50%.

[0097] The solvent-based two-component clear coating material (Z) may contain a coloring pigment as required to such an extent that transparency is not impaired, and may further contain an extender pigment, an ultraviolet absorber, a light stabilizer, a defoamer, a thickener, a rust preventive, a surface conditioner, and the like as appropriate.

[0098] The solvent-based two-component clear coating (Z) can be applied on the second color coating film by a method known per se, such as air spray coating, airless spray coating, rotary atomization coating, curtain coating, etc., and electrostatic application can be performed during coating. Among them, air spray coating, rotary atomization coating, etc. are preferred. The coating amount is preferably an amount of usually 25 μm or more and 50 μm or less, preferably 30 μm or more and 45 μm or less in terms of cured film thickness.

[0099] [Step (6)]

[0100] In step (6) of the present invention, the uncured first colored coating film, the uncured white coating film, the uncured interference color coating film, and the uncured clear coating film formed in steps (1) to (5) are heated at 75° C. to 100° C. to be cured simultaneously.

[0101] The curing of the above-mentioned uncured first colored coating film, uncured white coating film, uncured interference color coating film and uncured transparent coating film can be carried out by common coating film baking means (such as hot air heating, infrared heating, high-frequency heating, etc.). The heating time is not particularly limited, and is preferably generally about 10 to 60 minutes, especially about 15 to 40 minutes. Through this heating, the multilayer coating film composed of the uncured first colored coating film, the uncured white coating film, the uncured interference color coating film and the uncured transparent coating film can be cured simultaneously.

[0102] The heating temperature is more preferably 80°C or higher and 90°C or lower.

[0103] The multilayer coating film formed by steps (1) to (6) of the present invention has a brightness L*(15°) of 113 to 120, a luminous intensity Si(45°) of 3 to 5, and a reciprocal of graininess 1 / G of 0.4 to 0.5 when measured using a multi-angle spectrophotometer, and is white in color with excellent luminosity.

[0104] The brightness L*(15°) refers to the L* value measured by irradiating the measuring light at an angle of 45° relative to the axis perpendicular to the measuring object surface using a multi-angle spectrophotometer (trade name "MA68II", manufactured by X-rite Co., Ltd.) and receiving the light at an angle of 15° from the regular reflection angle to the direction of the measuring light. The higher the L*(15°), the higher the brightness of the obtained coating film, which means that the coating film is white.

[0105] The light intensity Si (45°) is the light intensity Si (45°) that can be calculated by using a multi-angle colorimeter (manufactured by BYK, trade name BYK-mac i), setting an imaging unit for imaging the surface of ...

[0106] The reciprocal of graininess, 1 / G, is the reciprocal of a granularity value that indicates the uniformity of light and dark areas, which is calculated by analyzing the image obtained by using a multi-angle colorimeter (manufactured by BYK, trade name, BYK-mac i) with a CCD chip under diffuse illumination in a white-painted hemisphere and using a histogram of brightness levels.

[0107] Example

[0108] The present invention will be described in detail below with reference to Examples and Comparative Examples. However, the present invention is not limited to these Examples. In addition, "parts" and "%" are based on mass.

[0109] <Manufacture of Aqueous Two-Component First Colored Paint (X)>

[0110] [Production Example 1]

[0111] 44.2 parts of a hydroxyl-containing polyester resin solution (a) (resin solid content: 20 parts), 60 parts of "JR-806" (trade name, manufactured by TAYCA Co., Ltd., rutile titanium dioxide), 1 part of "Carbon MA-100" (trade name, manufactured by Mitsubishi Chemical Corporation, carbon black), 30 parts of "Baryace B-35" (trade name, manufactured by Sakai Chemical Industry Co., Ltd., barium sulfate powder, average primary particle size 0.5 μm), 5 parts of "MICRO ACE S-3" (trade name, manufactured by TALC Co., Ltd., talc powder, average primary particle size 4.8 μm) and 45 parts of deionized water were mixed, the pH was adjusted to 8.0 with 2-(dimethylamino)ethanol, and the mixture was dispersed with a paint shaker for 30 minutes to obtain a pigment dispersion paste.

[0112] Next, 180 parts of the obtained pigment dispersion paste (resin solid content 20 parts), 66.7 parts of hydroxyl-containing acrylic resin dispersion (b) (resin solid content 20 parts), 11.1 parts of hydroxyl-containing polyester resin solution (a) (resin solid content 5 parts), "U-COATE UX-5210" (trade name, manufactured by Sanyo Chemical Industries, Ltd., polycarbonate-based water-based polyurethane resin, solid content 32%) 78 parts (resin solid content 25 parts) were added. , 0.1 part of tin catalyst "Scat-1W" (manufactured by Daiichi Sankyo Chemical Industry Co., Ltd., trade name, butyltin-based compound), 2-(dimethylamino)ethanol and deionized water for pH adjustment, and then the sulfonic acid-modified polyisocyanate compound solution (c) is uniformly mixed in an amount with an NCO / OH ratio of 1.7 to obtain an aqueous first coloring paint (X-1) with a viscosity of 55 seconds at a pH of 8.0 and 20°C by Ford Cup No. 4.

[0113] Here, the hydroxyl-containing polyester resin solution (a), the hydroxyl-containing acrylic resin dispersion (b), and the sulfonic acid-modified polyisocyanate compound solution (c) in Production Example 1 are described below.

[0114] (Hydroxy-containing polyester resin solution (a))

[0115] In a reaction vessel equipped with a thermometer, a thermostat, a stirring device, a reflux condenser and a water separator, 174 parts of trimethylolpropane, 327 parts of neopentyl glycol, 352 parts of adipic acid, 109 parts of isophthalic acid and 101 parts of hexahydrophthalic anhydride were added, and the temperature was raised from 160°C to 230°C over 3 hours. The generated condensation water was distilled off through a water separator while the temperature was maintained at 230°C to react until the acid value was 3 mgKOH / g or less. 59 parts of trimellitic anhydride was added to the reaction product, and the addition reaction was carried out at 170°C for 30 minutes. Then, an equivalent amount of 2-(dimethylamino)ethanol was added to the acid group for neutralization, and then deionized water was slowly added for water dispersion, thereby obtaining a hydroxyl-containing polyester resin solution having a solid content concentration of 45% and a pH of 7.2. The obtained hydroxyl-containing polyester resin had an acid value of 35 mgKOH / g and a hydroxyl value of 130 mgKOH / g.

[0116] (Hydroxy-containing acrylic resin dispersion (b))

[0117] 130 parts of deionized water and 0.52 parts of "Aqualon KH-10" (trade name, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) were added to a reaction container equipped with a thermometer, a thermostat, a stirrer, a reflux condenser, a nitrogen inlet tube and a dropping device, stirred and mixed in a nitrogen stream, and the temperature was raised to 80°C. Next, 1% of the total amount of the following monomer emulsion (1) and 5.3 parts of a 6% ammonium persulfate aqueous solution were introduced into the reaction container, and kept at 80°C for 15 minutes. Then, the remaining monomer emulsion (1) was added dropwise to the reaction container kept at the same temperature over 3 hours, and after the completion of the dropwise addition, the mixture was aged for 1 hour. Then, the following monomer emulsion (2) was added dropwise over 1 hour, and after aging for 1 hour, 40 parts of a 5% dimethylethanolamine aqueous solution was slowly added to the reaction vessel, and the mixture was cooled to 30°C, filtered and discharged through a 100-mesh nylon cloth, to obtain a hydroxyl-containing acrylic resin dispersion having an average particle size of 100 nm (measured at 20°C using a submicron particle size distribution measuring apparatus "COULTER N4" (trade name, manufactured by Beckman Coulter Co., Ltd.), diluted with deionized water, and solid content concentration of 30%). The obtained hydroxyl-containing acrylic resin had an acid value of 33 mgKOH / g and a hydroxyl value of 25 mgKOH / g.

[0118] -Monomer emulsion (1)-

[0119] 42 parts of deionized water, 0.72 parts of "Aqualon KH-10", 2.1 parts of methylenebisacrylamide, 2.8 parts of styrene, 16.1 parts of methyl methacrylate, 28 parts of ethyl acrylate and 21 parts of n-butyl acrylate were mixed and stirred to obtain a monomer emulsion (1).

[0120] -Monomer emulsion (2)-

[0121] 18 parts of deionized water, 0.31 parts of "Aqualon KH-10", 0.03 parts of ammonium persulfate, 5.1 parts of methacrylic acid, 5.1 parts of 2-hydroxyethyl acrylate, 3 parts of styrene, 6 parts of methyl methacrylate, 1.8 parts of ethyl acrylate and 9 parts of n-butyl acrylate were mixed and stirred to obtain a monomer emulsion (2).

[0122] (Sulfonic acid modified polyisocyanate compound solution (c))

[0123] 970 g (5.00 mol) of a polyisocyanate having an isocyanurate group and having an NCO content of 21.7% based on hexamethylene diisocyanate (HDI), an average NCO functionality of 3.5 (based on GPC), a monomer HDI content of 0.1% and a viscosity of 3000 mPas (23° C.), 30 g (0.14 mol) of 3-(cyclohexylamino)propanesulfonic acid, 17.4 g (0.14 mol) of dimethylcyclohexylamine and 254 g of 1-methoxypropyl 2-acetate were reacted under dry nitrogen at 80° C. for 5 hours with stirring to obtain a sulfonic acid-modified polyisocyanate compound solution having a solid content of 80% and an NCO content of 16.0%.

[0124] <Manufacture of water-based one-component white paint (Y-1)>

[0125] [Production Example 2]

[0126] Mix 44.2 parts of a hydroxyl-containing polyester resin solution (a) (20 parts of resin solid content), 100 parts of "JR-806" (trade name, manufactured by TAYCA Co., Ltd., rutile titanium dioxide) and 45 parts of deionized water, adjust the pH to 8.0 with 2-(dimethylamino)ethanol, and disperse with a paint stirrer for 30 minutes to obtain a pigment dispersion paste.

[0127] Next, 12.5 parts (10 parts in terms of resin solid content) of 80% solid content melamine resin (methyl-butyl mixed etherified melamine resin), 183 parts (55 parts in terms of resin solid content) of hydroxyl-containing acrylic resin dispersion (b) and 31 parts (10 parts in terms of resin solid content) of "U-COATED UX-5210" (trade name, manufactured by Sanyo Chemical Industries, Ltd., polycarbonate-based waterborne polyurethane resin, 32% solid content) were added to 189.2 parts (20 parts in terms of resin solid content) of the obtained pigment dispersion paste and 7.1 parts (5 parts in terms of resin solid content) of the hydroxyl-containing polyester resin (d) while stirring. Furthermore, dimethylethanolamine and deionized water were added to adjust the viscosity to 50 seconds measured by Ford Cup No. 4 at pH 8.0 and 20°C, to obtain a water-based white paint (Y-1-1). The water absorption of the uncured white coating film of the paint at 20°C was 5.7%.

[0128] Here, the hydroxyl-containing polyester resin (d) in the above-mentioned Production Example 4 is described.

[0129] (Hydroxy-containing polyester resin (d))

[0130] 109 parts of trimethylolpropane, 141 parts of 1,6-hexanediol, 126 parts of hexahydrophthalic anhydride and 120 parts of adipic acid were added to a reaction vessel equipped with a thermometer, a thermostat, a stirring device, a reflux condenser and a water separator, and the temperature was raised between 160°C and 230°C for 3 hours, and then a condensation reaction was carried out at 230°C for 4 hours. Next, in order to add a carboxyl group to the obtained condensation reaction product, 38.3 parts of trimellitic anhydride was further added, and after reacting at 170°C for 30 minutes, it was diluted with 2-ethyl-1-hexanol to obtain a hydroxyl-containing polyester resin solution with a solid content concentration of 70%. The acid value of the obtained hydroxyl-containing polyester resin was 46 mgKOH / g and the hydroxyl value was 150 mgKOH / g.

[0131] <Manufacturing of water-based single-liquid interference color coating (Y-2)>

[0132] [Production Example 3]

[0133] To 35.7 parts of a hydroxyl-containing polyester resin (d) (25 parts of resin solid content), 12.5 parts of a melamine resin (methyl-butyl mixed etherified melamine resin) having a solid content of 80% (10 parts in terms of resin solid content), 183 parts of a hydroxyl-containing acrylic resin dispersion (b) (55 parts in terms of resin solid content) and 31 parts of "UX-5210" (trade name, manufactured by Sanyo Chemical Industries, Ltd., a polycarbonate-based water-based polyurethane resin, 32% solid content) (10 parts in terms of resin solid content) were added while stirring. Thereafter, 15 parts of "Xirallic T61-10 MicroSilver" (trade name, manufactured by MERCK, titanium oxide-coated aluminum oxide flake pigment, average particle size 11.8 μm) as an optical interference pigment was added and dispersed while stirring, and further "PRIMAL ASE-60" (trade name, manufactured by Dow Chemical, thickener), dimethylethanolamine and deionized water were added to adjust the pH to 8.0, the coating solid content to 20%, and the viscosity to 45 seconds measured by Ford Cup No. 4 at 20°C, to obtain a water-based interference color coating (Y-2-1).

[0134] [Production Examples 4 to 14]

[0135] In Production Example 3, except that the type and content of the optical interference pigment and the solid content of the coating were changed as shown in Table 1 below, the same method as in Production Example 3 was carried out to obtain water-based interference color coatings (Y-2-2) to (Y-2-12) having a viscosity of 50 seconds measured by Ford Cup No. 4 at pH 8.00 and 20°C.

[0136] [Table 1]

[0137]

[0138]

[0139] (Note 1) “Xirallic T60-10 Crystal Silver”: trade name, manufactured by MERCK, titanium oxide-coated aluminum oxide flake pigment, average particle size 18.5 μm.

[0140] <Manufacturing of solvent-based two-component clear coating (Z)>

[0141] [Production Example 15]

[0142] 70 parts by weight of a hydroxyl-containing acrylic resin (e) in terms of solid content, an isocyanate crosslinking agent (Z2-1) (composed of 20% of a uretdione form of hexamethylene diisocyanate and 80% of a trimer or higher, with an NCO content of 20% and a viscosity of 800 mPa·s / 25° C.) at an NCO / OH ratio of 1.7 were uniformly mixed, and mixed with an organic solvent (a mixture of Solvesso 100 / methoxypropyl acetate in equal weights), and the viscosity was adjusted to 20 seconds as measured by Ford Cup No. 4 at 20° C., to obtain a clear coating (Z-1).

[0143] Here, the hydroxyl-containing acrylic resin (e) in Production Example 15 will be described.

[0144] (Hydroxy-containing acrylic resin (e))

[0145] The hydroxyl-containing acrylic resin (e) is an acrylic resin having a hydroxyl value of 120 mgKOH / g and a weight average molecular weight of 8000 obtained by free radical polymerization of 25 parts of styrene, 20 parts of n-butyl methacrylate, 30 parts of n-butyl acrylate, 24 parts of hydroxyethyl methacrylate and 1 part of acrylic acid by a conventional method.

[0146] [Production Example 16]

[0147] In Production Example 15, except that the amount of the isocyanate crosslinking agent (Z2-1) was adjusted so that the NCO / OH ratio was 1.5, the same procedure as in Production Example 15 was carried out to obtain a clear coating material (Z-2).

[0148] [Production Example 17]

[0149] In Production Example 15, 2 parts of "NANOBYK-3652" (trade name, linear alkyl-modified polydimethylsiloxane-modified silica particle dispersion, average particle size 20 nm, solid content concentration 31% (silica particle concentration 25%), manufactured by BYK) were added, and the same procedures as in Production Example 15 were carried out to obtain a clear coating (Z-3).

[0150] [Production Example 18]

[0151] A hydroxy-containing acrylic resin (e) of 70 parts by weight of solid content and an isocyanate crosslinking agent (Z2-2) (composed of less than 1% of uretdione of hexamethylene diisocyanate and 99% or more of trimer or above, with an NCO content of 20% and a viscosity of 1200 mPa·s / 25°C) at an NCO / OH ratio of 1.7 were uniformly mixed, and mixed with an organic solvent (a mixed solution of toluene / xylene of equal weight), and adjusted to a viscosity of 14 seconds measured at 20°C using Ford Cup No. 4 to obtain a clear coating (Z-4).

[0152] [Production Example 19]

[0153] In Production Example 15, except that the amount of the isocyanate crosslinking agent (Z2-1) was adjusted so that the NCO / OH ratio was 1.2, the same procedure as in Production Example 15 was carried out to obtain a clear coating material (Z-5).

[0154] [Production Example 20]

[0155] In Production Example 15, except that the amount of the isocyanate crosslinking agent (Z2-1) was adjusted so that the NCO / OH ratio was 2.2, the same procedure as in Production Example 15 was carried out to obtain a clear coating material (Z-6).

[0156] <Preparation of Test Plates 1 and 2>

[0157] As a metal component, a thermosetting epoxy resin-based cationic electrodeposition coating composition (trade name "エレクロン NT-360", manufactured by Kansai Paint Co., Ltd.) was electrodeposited on a zinc phosphate-treated cold-rolled steel plate (450 mm×300 mm×0.8 mm) in a film thickness of 20 μm, and heated at 170°C for 30 minutes to cure it.

[0158] As a plastic member, a primer "Softlex 3100" (trade name, manufactured by Kansai Paint Co., Ltd.) was air-sprayed onto a polypropylene plate (degreased) to a dry film thickness of 7 μm, and cured by heating at 80° C. for 30 minutes. Then, the surfaces of the metal member and the plastic member were degreased and placed adjacent to each other to prepare a test plate 1.

[0159] In addition, as a plastic member, a primer "Softlex 3100" (trade name, manufactured by Kansai Paint Co., Ltd.) was air-sprayed onto a NORYL GTX plate (degreased) to a dry film thickness of 7 μm, and cured by heating at 80° C. for 30 minutes. Then, the surfaces of the metal member and the plastic member were degreased, and they were placed adjacent to each other to prepare a test plate 2.

[0160] <Preparation of test coated panels>

[0161] [Example 1]

[0162] On the above test plate, the water-based first coloring paint (X-1) was electrostatically coated in a dry film thickness of 20 μm, and after standing at room temperature for 3 minutes, the water-based white paint (Y-1-1) was electrostatically coated in a dry film thickness of 10 μm, and stood at room temperature for 5 minutes, and the solid content of the coated film was changed to 55% by mass. Here, as described later, the water-based white paint (Y-1-1) was also coated on the aluminum foil for measuring the solid content of the coated film under the same coating conditions, and the solid content after standing at room temperature for 5 minutes was measured. Then, the water-based interference color paint (Y-2-1) was electrostatically coated in a dry film thickness of 5 μm, left at room temperature for 3 minutes, and then pre-dried at 80°C for 5 minutes. Then, the clear paint (Z-1) was electrostatically coated in a dry film thickness of 35 μm, left at room temperature for 5 minutes, and heated in an oven at 85°C for 20 minutes to obtain a test coating plate of Example 1 with a multilayer coating film.

[0163] Determination of the solid content of the coating film: A water-based white coating (Y-1-1) is applied to an aluminum foil of which the mass (M1) is measured in advance, and the water-based white coating (Y-1-1) is applied to the aluminum foil. After 5 minutes, the aluminum foil is recovered and the mass (M2) is measured. Next, the recovered aluminum foil is dried at 110°C for 60 minutes, and after naturally cooling to room temperature in a dryer, the mass (M3) of the aluminum foil is measured, and the solid content of the coating film is obtained according to the following formula.

[0164] Solid content of coating film (mass %) = {(M3-M1) / (M2-M1)}×100

[0165] [Example 2 to Example 13 and Comparative Example 1 to Comparative Example 11]

[0166] In Example 1, the standing time of the water-based white paint, the type and dry film thickness of the water-based interference color paint, and the type of the clear paint were changed as shown in Table 2 below. Otherwise, the same procedure as in Example 1 was followed to obtain test coated plates of Examples 2 to 13 and Comparative Examples 1 to 11.

[0167] [evaluate]

[0168] The following coating performance tests were performed on the test coated plates of Examples and Comparative Examples. The evaluation results are collectively shown in Tables 2 to 4.

[0169] (Smoothness)

[0170] The finish of each test coated plate was evaluated by smoothness. The Wd value measured by "Wave Scan DOI" (trade name, manufactured by BYK Gardner) was used to evaluate according to the following criteria. The smaller the Wd value, the higher the smoothness of the coated surface.

[0171] -Evaluation Criteria-

[0172] AA: Wd value less than 5.0

[0173] A: Wd value is 5.0 or more and 10.0 or less

[0174] C: Wd value is greater than 10.0

[0175] (Water resistance test: blistering)

[0176] A portion of each test coated plate was cut out and immersed in warm water at 40°C for 10 days, then pulled out and dried. The painted surface after pulling out was visually observed and the occurrence of blistering was evaluated according to the following criteria.

[0177] -Evaluation Criteria-

[0178] A: No bubbling occurs

[0179] B: Bubbling occurs in part

[0180] C: Foaming occurs all over the body

[0181] (Water resistance test: tightness)

[0182] A portion of each test coated plate was cut out, immersed in warm water at 40° C. for 10 days, pulled out and dried, and then the following adhesion evaluation was performed.

[0183] A cutter was used to cut into the coating surface of each test coated plate, and 100 squares of 2 mm × 2 mm were prepared. Cellophane tape was attached to the surface, and the number of remaining coating films on the squares after rapid peeling at 20°C was measured and evaluated according to the following criteria.

[0184] -Evaluation Criteria-

[0185] AA: 100 pcs (no peeling)

[0186] A: 100 pieces (partially peeled off)

[0187] B: 51 or more and less than 99

[0188] C: Less than 50

[0189] (Recoat adhesion)

[0190] Each test coated plate was left at room temperature for 7 days, the same coating was re-coated on the coated surface and cured, and then left at room temperature for 3 days. The above-mentioned adhesion evaluation was performed, and the number of remaining coating films was checked and evaluated according to the following criteria.

[0191] -Evaluation Criteria-

[0192] AA: 100 pcs (no peeling)

[0193] A: 100 pieces (partially peeled off)

[0194] B: 51 or more and less than 99

[0195] C: Less than 50

[0196] (Design)

[0197] -Brightness L*(15°)-

[0198] For each test coated plate, "MA68II" (trade name, manufactured by X-Rite Co., Ltd.) was used to measure L*(15°) and evaluate the brightness L*(15°) of the coating film. More specifically, the measuring light was irradiated at an angle of 45° relative to the axis perpendicular to the measuring object surface, and the brightness L* was measured for the light received at an angle of 15° from the regular reflection angle to the direction of the measuring light.

[0199] -Brightness Si(45°)-

[0200] For each test coated plate, the light intensity Si (45°) was measured and evaluated using "BYK-mac i" (trade name, manufactured by BYK Co., Ltd.). More specifically, a CCD chip for photographing the surface to be measured was set in a direction perpendicular to the plane direction of the surface to be measured, and light was irradiated to the surface to be measured at an angle of 45° relative to the perpendicular direction. The CCD chip photographed an image of the surface to be measured, and the obtained image was analyzed using an image analysis algorithm using a histogram of brightness levels, thereby calculating the light intensity Si (45°).

[0201] -The inverse of the graininess 1 / G-

[0202] For each test coated plate, the graininess G was measured using "BYK-mac i" (trade name, manufactured by BYK Co., Ltd.), and the reciprocal of the graininess 1 / G was evaluated. More specifically, the image was detected by a CCD chip under diffuse illumination in the hemisphere of the white coating, and the obtained image was analyzed using a histogram of brightness levels to perform calculations.

[0203] [Table 2]

[0204]

[0205] [Table 3]

[0206]

[0207]

[0208] [Table 4]

[0209]

[0210] As shown in Tables 2 and 3, it is found that the Examples formed by the multilayer coating film forming method of the present invention are excellent in smoothness, water resistance test, recoating adhesion, and design properties.

[0211] On the other hand, as shown in Table 4, Comparative Example 1, in which the content of titanium oxide-coated aluminum oxide flake pigment (B) having an average particle size of 10 μm to 14 μm in the aqueous one-component interference color coating type (Y-2) was 13 parts by mass, had poor design.

[0212] Comparative Example 2, in which the content of titanium oxide-coated aluminum oxide flake pigment (B) having an average particle size of 10 to 14 μm in the aqueous one-component interference color coating type (Y-2) was 23 parts by mass, was poor in design and water resistance test (foaming, adhesion).

[0213] The comparative example 3 in which the coating solid content was 16% among the water-based one-component interference color coating types (Y-2) was poor in design.

[0214] Among the water-based one-component interference color coating materials (Y-2), Comparative Example 4 in which the coating solid content was 24% was inferior in design.

[0215] Comparative Example 5, in which titanium oxide-coated aluminum oxide flake pigments were used in the water-based one-component interference color coating type (Y-2), was inferior in design.

[0216] Comparative Example 6, in which the standing time of the white coating film was 3 minutes and the solid content of the coated coating film was 48% by mass, was inferior in design.

[0217] Comparative Example 7, in which the cured film thickness of the interference coating film was 3 μm, was inferior in design properties.

[0218] Comparative Example 8 in which the cured film thickness of the interference coating film was 8 μm was poor in design properties.

[0219] Comparative Example 9, in which the solid content mass ratio of the polyisocyanate compound having a uretdione structure to the trimer or higher compound of diisocyanate in the solvent-based two-pack clear coating material (Z) was less than 1 / 99, was inferior in the water resistance test (foaming, adhesion).

[0220] Comparative Example 10 in which the NCO / OH ratio in the solvent-based two-component clear coating material (Z) was 1.2 was poor in the water resistance test (foaming, adhesion).

[0221] The solvent-based two-component clear coating material (Z) of Comparative Example 11 in which the NCO / OH ratio was 2.2 had poor recoat adhesion.

Claims

1. A method for forming a multilayer coating film, characterized in that: have: A step (1) of coating a first water-based two-component coloring paint (X) on both a metal component and a plastic component of an automobile outer panel to form an uncured first coloring coating film; Step (2) of coating the uncured first colored coating film obtained in step (1) with a water-based one-component white coating material (Y-1) to form an uncured white coating film; Step (3) of allowing the uncured white coating obtained in step (2) to stand until the solid content of the coating film is 50% by mass or more; A step (4) of coating the uncured white coating film having a solid content of 50% by mass or more obtained in the step (3) with a water-based one-component interference color coating material (Y-2) to form an uncured interference color coating film; A step (5) of coating the uncured interference color coating film obtained in the step (4) with a solvent-based two-component type clear coating material (Z) to form an uncured clear coating film; and a step (6) of simultaneously curing the uncured first colored coating film, the uncured white coating film, the uncured interference color coating film, and the uncured clear coating film formed in the steps (1) to (5) by heating at 75° C. or higher and 100° C. or lower, The aqueous single-liquid interference color coating (Y-2) contains a carrier-forming resin (A) and a titanium oxide-coated aluminum oxide flake pigment (B) having an average particle size of 10 μm or more and 14 μm or less, and contains 15 parts by mass or more and 21 parts by mass or less of the titanium oxide-coated aluminum oxide flake pigment (B) based on 100 parts by mass of the carrier-forming resin (A), and the coating solid content is 18% by mass or more and 22% by mass or less, The cured film thickness of the interference color coating film is 4 μm or more and 7 μm or less. The solvent-based two-component clear coating material (Z) contains a hydroxyl-containing acrylic resin (Z1) and a polyisocyanate compound (Z2), wherein the isocyanate group in the polyisocyanate compound (Z2) is contained in a ratio of 1.5 equivalents or more and 2.0 equivalents or less relative to 1 equivalent of the hydroxyl group in the hydroxyl-containing acrylic resin (Z1), and the polyisocyanate compound (Z2) contains a trimer or higher compound of a polyisocyanate compound having a uretdione structure and a diisocyanate in a ratio of 10 / 90 or more and 50 / 50 or less in terms of solid content mass ratio, The formed multilayer coating film has a brightness L*(15°) of 113 to 120, a luminous intensity Si(45°) of 3 to 5, and a reciprocal of graininess 1 / G of 0.4 to 0.5 when measured using a multi-angle colorimeter.

2. The method for forming a multilayer coating film according to claim 1, wherein: The aqueous one-liquid white paint (Y-1) contains a hydroxyl-containing polyester resin (Y1), a hydroxyl-containing acrylic resin (Y2), a hydroxyl-containing polyurethane resin (Y3) and a melamine resin (Y4), and the water absorption of the uncured white coating film at 20° C. is less than 6.5%.

3. The method for forming a multilayer coating film according to claim 1, wherein: The plastic component is pre-coated with a primer.

4. The method for forming a multilayer coating film according to claim 1, wherein: The plastic component is composed of a composite material of polyamide resin and modified polyphenylene ether resin.

5. The method for forming a multilayer coating film according to claim 1, wherein: The solvent-based two-component clear coating material (Z) further contains polysiloxane-modified silica particles (Z3) having an average primary particle diameter of 1 nm or more and 40 nm or less. 6 . A multilayer coating film obtained by the multilayer coating film forming method according to claim 1 .